Comparison of the Effectiveness of Acceptance and Commitment Therapy and Cognitive-Behavioral Therapy on Resilience in Patients with Breast Cancer - Sadeghpour, Mahdieh; Farokhzad , Pegah; Sarichlo, Mohammad Ebrahim; Ebrahimi Moghadam, Hossein (Iranian Journal of Neurodevelopmental Disorders, 2024)
Objective: The present study aimed to compare the effectiveness of Acceptance and Commitment Therapy (ACT) and Cognitive-Behavioral Therapy (CBT) on the resilience of patients with breast cancer. Methods and Materials: The statistical population of this quasi-experimental study included all women aged 25 to 65 years with breast cancer in Qazvin in 2022, among whom 45 participants were selected using convenience sampling and randomly assigned to three groups of 15 individuals. The research instruments included the Connor-Davidson Resilience Scale, the Acceptance and Commitment Therapy package (Hayes et al.), and the Cognitive-Behavioral Therapy package (Hawton et al.). Data analysis was performed at the descriptive level using mean and standard deviation, and at the inferential level using Multivariate Analysis of Covariance (MANCOVA) and Bonferroni post hoc test with SPSS-22 software. Findings: The results of the study showed a statistically significant difference in resilience levels between breast cancer patients in the experimental groups (ACT group and CBT group) and the control group (P < 0.05). In other words, both interventions, ACT and CBT, significantly improved resilience in breast cancer patients compared to the control group. Furthermore, the Bonferroni test results indicated no statistically significant difference in the effectiveness of ACT and CBT on resilience in breast cancer patients. Conclusion: Therefore, it can be concluded that both psychotherapies are beneficial for enhancing resilience in breast cancer patients.